Collaborative Governance: Trust Building Indicators in The “Fish Apartment” Community Empowerment Area Development (Cead) : Program in Malili District - Hidayat, Muhammad Hidayat Djabbari; Jeri M; Robby (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
The trust-building indicator is one of the stages in the collaboration process that considers collaboration to be more than just negotiations among various stakeholders. Beyond that, it is an effort to mutually build trust. Building trust is crucial and should be done as early as possible when the collaboration process begins to prevent egoism among the various institutions or organizations involved. The purpose of this research is to understand the collaborative governance process by analyzing the trust-building indicator in the implementation of the Community Empowerment Area Development Program through the